AN ANNOTATED TRANSLATION of VAN DRAANEN'S "FLIPPED" FROM ENGLISHINTO INDONESIAN - Shintia Pramudyaningtyas Ortantina (Jurnal Linguistik Terapan, 2022)
The existence of translation has broadened people's knowledge. People can acquire information about other countries' cultures easily, especially by reading novels. However, in the translation process, particularly in literary translation, translators may encounter some problems since translator must maintain the beauty of the source text in the target text. This research aims to find out what problems are encountered and how the problems are solved. In the process of translation of this novel, I encountered two main types of problems, namely problem in understanding and problem in transfer, but apparently, I also encountered problems both in understanding and transfer. The problems that I found were in the form of word, phrase, and clause. There were some ways that I took to solve the problems, such as looking up an online dictionary, searching on websites, and asking my advisors. To get a better understanding of the terms that I wanted to translate, I entered a keyword on Google and browse the image or watched the film which was adapted from this novel.